2014
DOI: 10.1371/journal.pcbi.1003675
|View full text |Cite
|
Sign up to set email alerts
|

BiP Clustering Facilitates Protein Folding in the Endoplasmic Reticulum

Abstract: The chaperone BiP participates in several regulatory processes within the endoplasmic reticulum (ER): translocation, protein folding, and ER-associated degradation. To facilitate protein folding, a cooperative mechanism known as entropic pulling has been proposed to demonstrate the molecular-level understanding of how multiple BiP molecules bind to nascent and unfolded proteins. Recently, experimental evidence revealed the spatial heterogeneity of BiP within the nuclear and peripheral ER of S. cerevisiae (comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 87 publications
1
10
0
Order By: Relevance
“…During the adaptive ER stress, a series of protective cellular actions, for example the Unfolded Protein Response, have been generated to restore the protein homeostasis in ER. The commonly accepted adaptive ER stress marker BIP is a chaperone protein that belongs to the HSP70 family [55]. Considering abnormal protein secretion or protein aggregation have been observed in SELENOF deficiency cases, together with our results that HSF1 up-regulated SELENOF during heat shock and adaptive ER stress, these indicated that SELENOF may play a protective role similar to the HSPs by handling the protein quality control.…”
Section: Discussionsupporting
confidence: 75%
“…During the adaptive ER stress, a series of protective cellular actions, for example the Unfolded Protein Response, have been generated to restore the protein homeostasis in ER. The commonly accepted adaptive ER stress marker BIP is a chaperone protein that belongs to the HSP70 family [55]. Considering abnormal protein secretion or protein aggregation have been observed in SELENOF deficiency cases, together with our results that HSF1 up-regulated SELENOF during heat shock and adaptive ER stress, these indicated that SELENOF may play a protective role similar to the HSPs by handling the protein quality control.…”
Section: Discussionsupporting
confidence: 75%
“…Pulling of the translocating polypeptide from inside the lumen may compel bulky structured domains that are still on the cytosolic side to collide with the pore entry, leading to their unfolding and unidirectional translocation into the lumen. There, the protein can reach the native state, assisted by soluble DNAJB11 and the ATP-fuelled unfoldases BIP (HSPA5) and HYOU (Matlack et al, 1997 ; Goloubinoff and De Los Rios, 2007 ; Griesemer et al, 2014 ; Melnyk et al, 2015 ).…”
Section: Hsp70/hsp110 Evolution and Cellular Functionsmentioning
confidence: 99%
“…The formation of DnaJ conglomerates at the aggregate surface might also provide the advantage to recruit several DnaK molecules in close proximity, provided that the J-domain is available for DnaK binding. Recruiting of several Hsp70 molecules close enough to form clusters at the aggregate surface, as shown for BiP [47], might enhance the disaggregation efficiency through their coordinated action via entropic pulling [48]. Supporting this interpretation is the finding that deletion of the G/F region in yeast Hsp40 Sis1 causes a defect in cell growth, without affecting its capacity to bind denatured substrates and to stimulate the Hsp70 ATPase activity.…”
Section: Discussionmentioning
confidence: 89%